Vascular Endothelial Growth Factor (VEGF) Prevents the Downregulation of the Cholinergic Phenotype in Axotomized Motoneurons of the Adult Rat - Acosta, Lourdes; Morcuende, Sara; Silva-Hucha, Silvia; Pastor, Angel M.; de la Cruz, Rosa R. (Frontiers in Molecular Neuroscience, 2018)
Vascular endothelial growth factor (VEGF) was initially characterized by its activity on the vascular system. However, there is growing evidence indicating that VEGF also acts as a neuroprotective factor, and that its administration to neurons suffering from trauma or disease is able to rescue them from cell death. We questioned whether VEGF could also maintain damaged neurons in a neurotransmissive mode by evaluating the synthesis of their neurotransmitter, and whether its action would be direct or through its well-known angiogenic activity. Adult rat extraocular motoneurons were chosen as the experimental model. Lesion was performed by monocular enucleation and immediately a gelatine sponge soaked in VEGF was implanted intraorbitally. After 7 days, abducens, trochlear and oculomotor nuclei were examined by immunohistochemistry against choline acetyltransferase (ChAT), the biosynthetic enzyme of the motoneuronal neurotransmitter acetylcholine. Lesioned motoneurons exhibited a noticeable ChAT downregulation which was prevented by VEGF administration. To explore whether this action was mediated via an increase in blood vessels or in their permeability, we performed immunohistochemistry against laminin, glucose transporter-1 and the plasmatic protein albumin. The quantification of the immunolabeling intensity against these three proteins showed no significant differences between VEGF-treated, axotomized and control animals. Therefore, the present data indicate that VEGF is able to sustain the cholinergic phenotype in damaged motoneurons, which is a first step for adequate neuromuscular neurotransmission, and that this action seems to be mediated directly on neurons since no sign of angiogenic activity was evident. These data reinforces the therapeutical potential of VEGF in motoneuronal diseases.